Cardiac Beriberi in an infant : An Unforgettable Dis - Hassan, Mahmuda; Mukti, Afsana; Haque, Hakimul; Khan, Masuma; Begum, Marium; Roy, Sudipta; Ahmed, Taslim Uddin; Ahmed, Ashraf Uddin; Tabassum, Sadia; Kabir, ARM Luthful; Rahman, Hamidur (Northern International Medical College Journal, 2018)
Abstract not available Northern International Medical College Journal Vol.9(2) Jan 2018: 315-317